Longer-term neurological and endocrine/metabolic conditions in the deepwater horizon oil spill coast guard cohort study: A principal component analysis - Hristina Denic-Roberts; Jordan McAdam; Lawrence S. Engel; Jeanine M. Buchanich; Rachel G. Miller; Evelyn O. Talbott; Dana L. Thomas; Glen A. Cook; Blake Hansen; Jill E. Emerick; Tina Costacou; Jennifer A. Rusiecki (International Archives of Occupational and Environmental Health, 2026)
Purpose Deepwater Horizon oil spill (DWHOS) responders potentially experienced multiple stressors. We examined associations between DWHOS deployment-related stressor patterns and neurological and endocrine/metabolic conditions among U.S. Coast Guard active duty responders who completed post-deployment surveys (n = 3102). Methods Deployment-related stressor patterns were identified using principal component analysis of self-reported stressors. Neurological and endocrine/metabolic outcomes were classified from military health encounter records. Associations between principal components (PCs) and incident outcomes (2010–2015) were estimated through Cox proportional hazards regression. Results A five-component solution explained 79.2% of the variance. PC1 (high physical/moderate chemical stressor pattern) was associated with migraine [adjusted hazard ratio (aHR): 1.25, 95% confidence interval (CI): 1.01–1.56]. PC2 (high crude oil/dispersant stressor pattern) was associated with several migraine/headache conditions including migraine with aura (1.54, 1.14–2.07), mononeuritis of upper limb and mononeuritis multiplex (1.36, 1.11–1.68), disorders of lipid metabolism (1.11, 1.01–1.23 ) and its subcategory other and unspecified hyperlipidemia (1.11, 1.01–1.24), and dysmetabolic syndrome X (1.74, 1.19–2.54). PC3 (high fatigue/moderate chemical inhalation stressor pattern) was associated with several migraine/headache conditions (aHR range: 1.18–1.60), disorders of lipid metabolism (1.11, 1.00–1.23) including other and unspecified hyperlipidemia (1.13, 1.01–1.26) , and overweight and obesity (1.13, 1.00–1.27). PC4 (high anxiety/modest fatigue stressor pattern) was associated with abnormality of gait (1.34, 1.03–1.73). PC5 (high back pain) was associated with mononeuritis of lower limb, several balance and gait-related conditions , thyroid disorders, and obesity (aHRs range: 1.16–1.67). Conclusion Oil spill response stressor patterns were associated with increased risks of multiple longer-term neurological and endocrine/metabolic conditions, with associations varying by PC.

Understanding the influence of environmentally persistent free radical location on reactive oxygen species generation in soils - Myron L. Lard; Sarah E. Eichler; Lavrent Khachatryan; Randall Hall; Stephania A. Cormier; Robert L. Cook; Jennifer Richmond-Bryant (Chemosphere, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

A Dominant Founder Lineage Has Possible Fitness Costs for the Endangered Mexican Grey Wolf - Yeraldi Loera; Manisha Khakoo; Emily Krueckeberg; Ingrid G. Nilsson; Zehao Wu; Maggie Dwire; Jennifer Adams; Lisette Waits; John K. Oakleaf; Mariel L. Campbell; Jonathan L. Dunnum; Joseph A. Cook; et al. (Molecular Ecology, 2026)
The Mexican grey wolf ( Canis lupus baileyi ) is an endangered and genetically distinct subspecies of grey wolf adapted to the warm climates of the southwestern United States and Mexico. Following centuries of eradication efforts, Mexican grey wolves were protected under the Endangered Species Act in 1976, prompting an international ex situ breeding program to preserve their genetic legacy. Seven remnant wolves founded the three distinct lineages of this program: McBride, Ghost Ranch, and Aragón. However, concerns of rising inbreeding levels motivated the implementation of inter‐lineage pairings to decelerate genetic erosion. To evaluate the genetic health of the ex situ managed population, we analysed genome‐wide variation across several generations of breeding wolves and their descendants ( n = 179). Despite ongoing conservation interventions, we found a sharp decline in effective population size over the past 50 generations. However, estimates of inbreeding diminished over time following the inter‐lineage pairings, reflecting efficient pedigree management or potential fitness costs of inbreeding depression, as higher levels of inbreeding and autozygosity were associated with reduced lifespan and reproductive performance. Increasing contributions of Ghost Ranch and Aragón ancestry also aided in reducing levels of inbreeding observed in the more genetically distinct McBride lineage. These findings highlight the challenges of maintaining genetic diversity in bottlenecked populations, reveal fine‐scale patterns of inbreeding within the pedigree and underscore the urgent need to preserve genetic contributions from all founder lineages. Genomic insights from this study can guide breeding strategies to reduce kinship, balance ancestry and mitigate inbreeding depression, safeguarding the evolutionary legacy and the long‐term persistence of the Mexican grey wolf.

Wind speed and direction influence beach plastic accumulation patterns on remote Christmas Island - Jennifer L. Lavers; Hayley Cook; Casey Woodward; Heidi L. Tait; Jack Rivers-Auty (Marine Pollution Bulletin, 2026)

Exploring Marine Mammal Cognition as a Conservation Tool - Gordon B. Bauer; Peter F. Cook; Heidi E. Harley; Jason Bruck; Mel Cosentino; Charles J. Deutsch; Nicola Erdsack; Wendi Fellner; Tabitha Gunnars; Heather Manitzas Hill; Sonia V. Kumar; Malin K. Lilley; et al. (Marine Mammal Science, 2026)
Cognition is an animal's real‐time adaptation system for responding to change. Rapid environmental change, often anthropogenic, is expanding the range and severity of challenges confronting wild animals. Effective conservation requires a multifaceted approach that includes animals' capacities. Large‐brained, long‐lived animals such as marine mammals often have extensive capability to adaptively modify their behavior due to their cognition, which comprises the mechanisms of information acquisition, processing, and flexible action. Consequently, current behavior need not be a final predictor of future behavior for these animals. This flexibility provides an underutilized and under examined point of leverage for humans interested in improving life outcomes for wild animals. In this team‐written, interdisciplinary paper, we argue that application of cognitive approaches may facilitate many conservation efforts directed toward marine mammals. Starting with a workshop on this topic at the 24th Biennial Conference on the Biology of Marine Mammals, scientists representing a wide range of disciplinary expertise addressed eight different conservation concerns for six marine mammal species and provided potential cognitive explanations of and interventions aimed at related behavior. Our treatment highlights the value of integrated laboratory and field research, and the importance of tight lines of communication between scientists and conservation managers.

The Properties of Individual Fire Events Are Essential for Understanding Global Fire Regimes - Adam L. Mahood; Ty Tuff; Megan E. Cattau; Virginia Iglesias; Thomas E. Hanson; Jilmarie Stephens; Nayani Ilangakoon; Maxwell C. Cook; R. Chelsea Nagy; David Barnard; E. Natasha Stavros; Amy DeCastro; et al. (Global Ecology and Biogeography, 2025)
Aim As fire activity changes globally, we need to better understand the spatial and temporal characteristics of the individual events that, when aggregated, constitute fire regimes. Most global studies analyze point detections of burned area, without delineating or considering the properties of individual events. Furthermore, there is a critical need to understand fire patterns within the context of the geopolitical boundaries within which fires are managed. Location Global. Time Period 2003–2020. Major Taxa Studied Fire. Methods We divided 241 countries by Köppen‐Geiger climate classifications and quantified four event‐based fire regime metrics: size, duration, and mean and maximum growth rate; and four area‐based metrics: burned area, number of fires, season length, and season peak. We examined the correlations among fire regime components, and between each fire regime component and climate normals. We quantified temporal trends, and used mixed models to analyze how climate and landcover change were associated with event‐based components of fire regimes. Results Event‐based metrics were weakly correlated with area‐based metrics. Countries with warmer and less variable climates had high burned area, more fire events, longer season lengths and shorter event durations. Countries with high annual temperature range and low precipitation tended to have fewer events but larger fires that were faster‐spreading and occurred later in the year. The growth rate and size of individual fire events are increasing in 18% and 21% of regions we analysed, respectively. Interannual variability in size and growth rate was associated with aridity increases in boreal areas, and landcover changes in arid areas. Main Conclusions Drivers of burned area and fire seasonality are well understood but largely unrelated to the properties of individual events. A more detailed understanding of the spatial and temporal aspects of fire events at broad scales will assist fire management efforts in preparing for a warmer future.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Threat assessment for Pacific sand lance (Ammodytes personatus) in the Salish Sea - Jacqueline R. Huard; Victoria Hemming; Matthew R. Baker; Jennifer Blancard; Ian Bruce; Sarah Cook; Gail K. Davoren; Phillip Dionne; Virginia East; J. Mark Hipfner; Nicola R. Houtman; Brian A. Koval; et al. (Frontiers in Marine Science, 2024)
Like many forage fish species, Pacific sand lance ( Ammodytes personatus ) play a key role in nearshore marine ecosystems as an important prey source for a diverse array of predators in the northeastern Pacific. However, the primary threats to Pacific sand lance and their habitat are poorly defined due to a lack of systematic data. Crucial information needed to assess their population status is also lacking including basic knowledge of their local and regional abundance and distribution. Sand lance are currently listed as ‘not evaluated’ under the IUCN red list and they have not been assessed by US and Canadian agencies. This hampers management and policy efforts focused on their conservation. To address this knowledge gap, we conducted a three-part, structured expert elicitation to assess the vulnerability of Salish Sea sand lance populations. Experts were asked to list and rank key threats to Salish Sea sand lance and/or their habitat, to further quantify the vulnerability of sand lance to identified threats using a vulnerability matrix, and to predict the population trajectory in 25 years from today. Impacts associated with climate change (e.g. sea level rise, sea temperature rise, ocean acidification, and extreme weather) consistently ranked high as threats of concern in the ranking exercise and quantified vulnerability scores. Nearly every expert predicted the population will have declined from current levels in 25 years. These results suggest sand lance face numerous threats and may be in decline under current conditions. This research provides vital information about which threats pose the greatest risk to the long-term health of sand lance populations and their habitat. Managers can use this information to prioritize which threats to address. Future research to reliably quantify population size, better understand the roles of natural and anthropogenic impacts, and to identify the most cost-effective actions to mitigate multiple threats, is recommended.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Association of diet with per- and polyfluoroalkyl substances in plasma and human milk in the New Hampshire Birth Cohort Study - Yuting Wang; Jiang Gui; Caitlin G. Howe; Jennifer A. Emond; Rachel L. Criswell; Lisa G. Gallagher; Carin A. Huset; Lisa A. Peterson; Julianne Cook Botelho; Antonia M. Calafat; Brock Christensen; Margaret R. Karagas; et al. (Science of The Total Environment, 2024)

Small-scale movements and site fidelity of two sympatric sea turtle species at a remote atoll - Cheryl L. Sanchez; Nancy Bunbury; Jeanne A. Mortimer; Luke A’Bear; Jennifer Appoo; Michael Betts; Rainer von Brandis; Lorraine Cook; Janske van de Crommenacker; Jock C. Currie; Naomi Doak; Frauke Fleischer-Dogley; et al. (Marine Biology, 2024)
Understanding natural movement patterns and ecological roles of marine megafauna is a research priority best studied in areas with minimal human impact. The spatial distribution patterns specifically for immature turtles at foraging grounds have been highlighted as a research gap for effective management and conservation strategies for sea turtle populations. Capture–mark–recapture (CMR) records ( n = 2287) of 1672 immature green ( Chelonia mydas ) ( n = 1158) and hawksbill turtles ( Eretmochelys imbricata ) ( n = 514) from a long-term (1981–2021) in-water CMR program at Aldabra Atoll, Seychelles, were analyzed for 10 sites (0.35–25 km apart). Site fidelity was not correlated with either season or turtle size. Green turtles had lower site fidelity than hawksbill turtles. Green turtles showed avoidance (i.e., opposite of fidelity) of three sites, while hawksbill turtles displayed high fidelity to two sites. Sites displaying non-random behavior (avoidance and/or fidelity) did not share the same benthic habitat types. Results indicate that fidelity can be detected at a fine scale with CMR, but that further exploration into the habitat characteristics of the sites and the ecological roles of both species at the atoll is needed.

Effects of establishment fertilization on Landsat-assessed leaf area development of loblolly pine stands - Matthew N. House; Randolph H. Wynne; Valerie A. Thomas; Rachel L. Cook; David R. Carter; Jennifer H. Van Mullekom; Jim Rakestraw; Todd A. Schroeder (Forest Ecology and Management, 2024)

Transmission mode predicts coinfection patterns of insect‐specific viruses in field populations of the Queensland fruit fly - Stephen R. Sharpe; Jennifer L. Morrow; James M. Cook; Alexie Papanicolaou; Markus Riegler (Molecular Ecology, 2024)
Insect‐specific viruses (ISVs) can affect insect health and fitness, but can also interact with other insect‐associated microorganisms. Despite this, ISVs are often studied in isolation from each other, in laboratory populations. Consequently, their diversity, prevalence and associations with other viruses in field populations are less known, yet these parameters are important to understanding virus epidemiology. To help address this knowledge gap, we assessed the diversity, prevalence and coinfections of three ISVs (horizontally transmitted cripavirus, biparentally transmitted sigmavirus and maternally transmitted iflavirus) in 29 field populations of Queensland fruit fly, Australia's most significant horticultural pest, in the context of their different transmission modes. We detected new virus variant diversity. In contrast to the very high virus prevalence in laboratory populations, 46.8% of 293 field flies carried one virus and 4.8% had two viruses. Cripavirus and sigmavirus occurred in all regions, while iflavirus was restricted to subtropical and tropical regions. Cripavirus was most prevalent (37.5%), followed by sigmavirus (13.7%) and iflavirus (4.4%). Cripavirus coinfected some flies with either one of the two vertically transmitted viruses. However, sigmavirus did not coinfect individuals with iflavirus. Three different modelling approaches detected negative association patterns between sigmavirus and iflavirus, consistent with the absence of such coinfections in laboratory populations. This may be linked with their maternal transmission and the ineffective paternal transmission of sigmavirus. Furthermore, we found that, unlike sigmavirus and iflavirus, cripavirus load was higher in laboratory than field flies. Laboratory and mass‐rearing conditions may increase ISV prevalence and load due to increased transmission opportunities. We conclude that a combination of field and laboratory studies is needed to uncover ISV interactions and further our understanding of ISV epidemiology.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Carbon and Lipid Contents of the Copepod Calanus finmarchicus Entering Diapause in the Fram Strait and Their Contribution to the Boreal and Arctic Lipid Pump - Geraint A. Tarling; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn Barbara Cook; Finlo R. Cottier; Victoria Dewar-Fowler; Jennifer J. Freer; Laura Gerrish; Magnus L. Johnson; Kim S. Last; Penelope Kate Lindeque; et al. (Frontiers in Marine Science, 2022)
The boreal copepod Calanus finmarchicus sequesters substantial amounts of carbon (C) in the deep layers of the North Atlantic Ocean through their contribution to the “lipid pump.” This pump is driven by these zooplankton descending from the surface layers to spend prolonged periods at depth during which time they metabolise substantial lipid reserves and a fraction suffer mortality. C. finmarchicus is principally a boreal species but is expatriated by currents flowing northwards into Arctic regions such as the Fram Strait, where it is now able to complete its life cycle. We considered how this expansion to its distributional range adds to the estimated magnitude of the lipid pump. Field sampling in the Fram Strait found C. finmarchicus abundance to be spatially variable with high values, equivalent to those reported for core distributional areas further south, found mainly in the eastern region. Lipid reserve levels were sufficient for many individuals to survive the overwintering period and reproduce the following spring. In accordance with abundance patterns, lipid pump magnitude was greater in the Eastern Fram Strait (2.04 g C m −2 year −1 ) compared to the Western Fram Strait (0.33 g C m −2 year −1 ). At least for the eastern region, these rates are similar to those reported for this species elsewhere (average of 4.35 g C m −2 year −1 ). When extrapolated to the wider spatial area of the Fram Strait, the lipid pump generated by this species in this ocean sector amounts to 0.3 Mt C year −1 . Although constituting a modest proportion of the total C. finmarchicus lipid pump of 19.3 Mt C year −1 , it indicates that the continued northwards expansion of this species will act to increase the size of its lipid pump, which may counteract that lost through the northwards retreat of its Arctic congeners, Calanus glacialis and Calanus hyperboreus .

Ethnicity, socioeconomic status, income inequality, and colorectal cancer outcomes: evidence from the 4C2 collaboration - Cathy J. Bradley; Amy Anderson-Mellies; Evelinn A. Borrayo; Jennifer Anne Doherty; Omar A. Escontrías; David O. Garcia; Shiraz I. Mishra; Andrew L. Sussman; Cynthia A. Thomson; David W. Wetter; Linda S. Cook (Cancer Causes & Control, 2022)

Can a key boreal Calanus copepod species now complete its life-cycle in the Arctic? Evidence and implications for Arctic food-webs - Geraint A. Tarling; Jennifer J. Freer; Neil S. Banas; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn B. Cook; Finlo R. Cottier; Malin Daase; Magnus L. Johnson; Kim S. Last; Penelope K. Lindeque; et al. (Ambio, 2022)
The changing Arctic environment is affecting zooplankton that support its abundant wildlife. We examined how these changes are influencing a key zooplankton species, Calanus finmarchicus , principally found in the North Atlantic but expatriated to the Arctic. Close to the ice-edge in the Fram Strait, we identified areas that, since the 1980s, are increasingly favourable to C. finmarchicus . Field-sampling revealed part of the population there to be capable of amassing enough reserves to overwinter. Early developmental stages were also present in early summer, suggesting successful local recruitment. This extension to suitable C. finmarchicus habitat is most likely facilitated by the long-term retreat of the ice-edge, allowing phytoplankton to bloom earlier and for longer and through higher temperatures increasing copepod developmental rates. The increased capacity for this species to complete its life-cycle and prosper in the Fram Strait can change community structure, with large consequences to regional food-webs.

Effects of methylphenidate on reinforcement learning depend on working memory capacity - Mojtaba Rostami Kandroodi; Jennifer L. Cook; Jennifer C. Swart; Monja I. Froböse; Dirk E. M. Geurts; Abdol-Hossein Vahabie; Majid Nili Ahmadabadi; Roshan Cools; Hanneke E. M. den Ouden (Psychopharmacology, 2021)
Rationale Brain catecholamines have long been implicated in reinforcement learning, exemplified by catecholamine drug and genetic effects on probabilistic reversal learning. However, the mechanisms underlying such effects are unclear. Objectives and methods Here we investigated effects of an acute catecholamine challenge with methylphenidate (20 mg, oral) on a novel probabilistic reversal learning paradigm in a within-subject, double-blind randomised design. The paradigm was designed to disentangle effects on punishment avoidance from effects on reward perseveration. Given the known large individual variability in methylphenidate’s effects, we stratified our effects by working memory capacity and trait impulsivity, putatively modulating the effects of methylphenidate, in a large sample ( n = 102) of healthy volunteers. Results Contrary to our prediction, methylphenidate did not alter performance in the reversal phase of the task. Our key finding is that methylphenidate altered learning of choice-outcome contingencies in a manner that depended on individual variability in working memory span. Specifically, methylphenidate improved performance by adaptively reducing the effective learning rate in participants with higher working memory capacity. Conclusions This finding emphasises the important role of working memory in reinforcement learning, as reported in influential recent computational modelling and behavioural work, and highlights the dependence of this interplay on catecholaminergic function.

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Sex Differences in Pediatric Poisonings by Age Group: a Toxicology Investigators’ Consortium (ToxIC) Analysis (2010–2016) - Gillian A. Beauchamp; Jennifer L. Carey; Matthew D. Cook; Robert D. Cannon; Kenneth D. Katz; Jennifer Yoon; Hope Kincaid; Brittany J. Ely; Emily Pollack; Richard J. Mazzaccaro; Marna Rayl Greenberg (Journal of Medical Toxicology, 2020)

Implementation of a Systematic Tumor Screening Program for Lynch Syndrome in an Integrated Health Care Setting - Elizabeth V. Clarke; Kristin R. Muessig; Jamilyn Zepp; Jessica E. Hunter; Sapna Syngal; Louise S. Acheson; Georgia L. Wiesner; Susan K. Peterson; Kellene M. Bergen; Elizabeth Shuster; James V. Davis; Jennifer L. Schneider; et al. (Familial Cancer, 2019)

Codivergence of the primary bacterial endosymbiont of psyllids versus host switches and replacement of their secondary bacterial endosymbionts - Aidan A. G. Hall; Jennifer L. Morrow; Caroline Fromont; Martin J. Steinbauer; Gary S. Taylor; Scott N. Johnson; James M. Cook; Markus Riegler (Environmental Microbiology, 2016)
Summary Coevolution between insects and bacterial endosymbionts contributes to the success of many insect lineages. For the first time, we tested for phylogenetic codivergence across multiple taxonomic scales, from within genera to superfamily between 36 psyllid species of seven recognised families (Hemiptera: Psylloidea), their exclusive primary endosymbiont Carsonella and more diverse secondary endosymbionts (S‐endosymbionts). Within Aphalaridae, we found that Carsonella and S‐endosymbionts were fixed in one Glycaspis and 12 Cardiaspina populations. The dominant S‐endosymbiont was Arsenophonus , while Sodalis was detected in one Cardiaspina species. We demonstrated vertical transmission for Carsonella and Arsenophonus in three Cardiaspina species. We found strong support for strict cospeciation and validated the informative content of Carsonella as extended host genome for inference of psyllid relationships. However, S‐endosymbiont and host phylogenies were incongruent, and displayed signs of host switching and endosymbiont replacement. The high incidence of Arsenophonus in psyllids and other plant sap‐feeding Hemiptera may be due to repeated host switching within this group. In two psyllid lineages, Arsenophonus and Sodalis genes exhibited accelerated evolutionary rates and AT‐biases characteristic of long‐term host associations. Together with strict vertical transmission and 100% prevalence within host populations, our results suggest an obligate, and not facultative, symbiosis between psyllids and some S‐endosymbionts.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Cardiorespiratory fitness is associated with brain structure, cognition, and mood in a middle-aged cohort at risk for Alzheimer’s disease - Elizabeth A. Boots; Stephanie A. Schultz; Jennifer M. Oh; Jordan Larson; Dorothy Edwards; Dane Cook; Rebecca L. Koscik; Maritza N. Dowling; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; et al. (Brain Imaging and Behavior, 2015)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Genetic variation in sex-steroid receptors and synthesizing enzymes and colorectal cancer risk in women - Jennifer Lin; Robert Y. L. Zee; Kuang-Yu Liu; Shumin M. Zhang; I-Min Lee; JoAnn E. Manson; Edward Giovannucci; Julie E. Buring; Nancy R. Cook (Cancer Causes & Control, 2010)

Cryptic seedling herbivory by nocturnal introduced generalists impacts survival, performance of native and exotic plants - Sharon Y. Strauss; Maureen L. Stanton; Nancy C. Emery; Carrie A. Bradley; Alexandra Carleton; Dylan R. Dittrich-Reed; Olivia A. Ervin; Levi N. Gray; Andrew M. Hamilton; Jennifer Harrington Rogge; Skye D. Harper; Kimberley Cook Law; et al. (Ecology, 2009)
Although much of the theory on the success of invasive species has been geared at escape from specialist enemies, the impact of introduced generalist invertebrate herbivores on both native and introduced plant species has been underappreciated. The role of nocturnal invertebrate herbivores in structuring plant communities has been examined extensively in Europe, but less so in North America. Many nocturnal generalists (slugs, snails, and earwigs) have been introduced to North America, and 96% of herbivores found during a night census at our California Central Valley site were introduced generalists. We explored the role of these herbivores in the distribution, survivorship, and growth of 12 native and introduced plant species from six families. We predicted that introduced species sharing an evolutionary history with these generalists might be less vulnerable than native plant species. We quantified plant and herbivore abundances within our heterogeneous site and also established herbivore removal experiments in 160 plots spanning the gamut of microhabitats. As 18 collaborators, we checked 2000 seedling sites every day for three weeks to assess nocturnal seedling predation. Laboratory feeding trials allowed us to quantify the palatability of plant species to the two dominant nocturnal herbivores at the site (slugs and earwigs) and allowed us to account for herbivore microhabitat preferences when analyzing attack rates on seedlings. The relationship between local slug abundance and percent cover of five common plant taxa at the field site was significantly negatively associated with the mean palatability of these taxa to slugs in laboratory trials. Moreover, seedling mortality of 12 species in open‐field plots was positively correlated with mean palatability of these taxa to both slugs and earwigs in laboratory trials. Counter to expectations, seedlings of native species were neither more vulnerable nor more palatable to nocturnal generalists than those of introduced species. Growth comparison of plants within and outside herbivore exclosures also revealed no differences between native and introduced plant species, despite large impacts of herbivores on growth. Cryptic nocturnal predation on seedlings was common and had large effects on plant establishment at our site. Without intensive monitoring, such predation could easily be misconstrued as poor seedling emergence.

Marine Metapopulations - Celeste Benham; Alison M. Cawood; Geoffrey S. Cook; Ange Darnell; Peter C. Davison; Miriam C. Goldstein; Ayana Elizabeth Johnson; Talina Konotchick; Elisa M. Maldonado; Alexis L. Pasulka; Jennifer C. Prairie; Serena M. Moseman; et al. (Marine Ecology, 2008)